Tax Regime in Free Economic Zones and Its Impact on Regional Competitiveness - Kulimova Khusnida Makhsud Kizi; Karimova Shaxnoza Uktamovna; Atadjanov Kadambay Sapayevich; Yusupov Sherzodbek Baxtiyor Ugli (Indonesian Journal Publisher, 2025)
In recent years, the practice of establishing free economic zones (FEZs) has been actively developing in the Republic of Uzbekistan with the aim of eliminating asymmetric conditions in regional economic development, attracting foreign and domestic investments, and modernizing local production. These zones are viewed as an important infrastructural and fiscal tool for addressing economic differentiation issues in the country, reducing unemployment, and increasing export volumes. Particularly, the tax incentives and preferential regimes being implemented within FEZs are creating favorable conditions for investors. However, the question of how these benefits impact long-term economic stability and interregional competitiveness has not yet been sufficiently researched. This article provides an in-depth analysis of the real economic efficiency of tax policies in Special Economic Zones (SEZs), their role in intensifying investment competition among regions, and their impact on local economic activity. The study evaluates the performance of existing free economic zones in Uzbekistan (Angren, Navoi, Jizzakh, and others) based on statistical data, conducts a comparative analysis with international experiences (China, UAE, Poland), and identifies strengths and weaknesses through SWOT analysis. As a result, the article proposes recommendations aimed at enhancing regional economic competition through SEZs, optimizing tax policies, and promoting strategic development. The significance of the article lies in its provision of theoretical and practical foundations for establishing a competitive fiscal environment and creating sustainable economic zones in Uzbekistan. It can be valuable not only for economists and policymakers but also for investors and representatives of regional administrations